Silencing of Transposable Elements by piRNAs in Drosophila: An Evolutionary Perspective - Luo, Shiqi (Genomics Proteomics Bioinformatics, 2017)
Transposable elements (TEs) are DNA sequences that can move within the genome. TEs have greatly shaped the genomes, transcriptomes, and proteomes of the host organisms through a variety of mechanisms. However, TEs generally disrupt genes and destabilize the host genomes, which substantially reduce fitness of the host organisms. Understanding the genomic distribution and evolutionary dynamics of TEs will greatly deepen our understanding of the TE-mediated biological processes. Most TE insertions are highly polymorphic in Drosophila melanogaster, providing us a good system to investigate the evolution of TEs at the population level. Decades of theoretical and experimental studies have well established “transposition-selection” population genetics model, which assumes that the equilibrium between TE replication and purifying selection determines the copy number of TEs in the genome. In the last decade, P-element-induced wimpy testis (PIWI)-interacting RNAs (piRNAs) were demonstrated to be master repressors of TE activities in Drosophila. The discovery of piRNAs revolutionized our understanding of TE repression, because it reveals that the host organisms have evolved an adaptive mechanism to defend against TE invasion. Tremendous progress has been made to understand the molecular mechanisms by which piRNAs repress active TEs, although many details in this process remain to be further explored. The interaction between piRNAs and TEs well explains the molecular mechanisms underlying hybrid dysgenesis for the I-R and P-M systems in Drosophila, which have puzzled evolutionary biologists for decades. The piRNA repression pathway provides us an unparalleled system to study the co-evolutionary process between parasites and host organisms.